MODEL DEVELOPMENT OF PHYSICAL EXERCISE GOALKEEPER OF FOOTBALL WITH CIRCUIT - Rizki Apriliyanto; Mulyana Mulyana; James Tangkudung (Program Pascasarjana Universitas Negeri Jakarta, 2017)
This study aims to develop models of physical exercise soccer goalie by using the circuit method. Research development is packaged in the form of circuit training models to improve the physical condition of football goalkeeper. Methods used are research and development (Research and Development) of the Borg & Gall with 10 steps. Feasibility models and evaluated by five expert sports. Those are 2 experts of coaching and 3 experts of goalkeeper. While the subject of research is the goalkeeper in Banyuwangi. This research begins with needs analysis, planning, product, testing, revision and final products. The results show that this model is feasible to use the product goalkeeper. In the test results for small groups and large groups can be explained that the model as a whole can do well. In a test of the effectiveness of the mean value for the group amounted to 42 221 circuit and the value of the conventional group amounted to 33 167 t-count value 3,447 such results can be declared effective circuit training models to improve the physical abilities keeper.It shows that the model of physical exercise with circuit can be used by the goalkeeper in football and can effectively improve the physical abilities soccer goalkeeper. Keywords: Exercise Models, Methods Circuits, Physical Condition.